(untitled) (Quinto Sol, 2013)
During the first years in power, peronism builds its identity from a matrix strongly directed from the national State, subjecting to its control the provincial States and the local peronisms that showed certain incompatible features of heterogeneity with the bias that Perón stamped to its political movement from the nation. Such a process reaches its maturity in 1949 with the reform of the national constitution and provincial constitutions. In that context, this article analyses the process of constitutional reform in the Province of Santa Fe, focusing on the constitutional tradition of the province, the local political system conflicts and especially the one that crosses the official peronism, and the tense relationship between the local power and the national one.